Comparison of effectiveness and tolerability of two oral low-dose formulations containing 1 mg of 17β-estradiol and either dydrogesterone or norethisterone acetate applied as continuous combined hormonal therapy in peri- and postmenopausal women - Paszkowski, Tomasz (Menopause Review/Przegląd Menopauzalny, 2006)
Objective: To compare the effectiveness and tolerability profile of two oral low-dose formulations containing 1 mg of 17β-estradiol and either dydrogesterone or norethisterone acetate applied as continuous combined hormonal therapy (ccHT) in peri- and postmenopausal women. Material and methods: The studied population consisted of 60 peri- or postmenopausal women aged 45-55 qualified for the continuous combined hormonal therapy. The patients were divided in two equally numerous groups receiving either Femoston Conti® or Activelle®. The following parameters were evaluated during the 3 months observation period: menopausal symptoms (Greene Scale), depressive mood (Beck’s Inventory), sexual life quality (Female Sexual Function Index) and the presence of unwanted effects. Results and conclusions: 1. Low-dose oral hormonal therapy with the use of 1 mg estradiol and either dydrogesterone or norethisterone acetate (NETA) effectively and rapidly eliminates climacteric symptoms of both vasomotoric and psychogenic character. 2. The use of biologically strong progestagen, such as NETA, in ccHT results in better bleeding profile as compared to the use of dydrogesterone. 3. After 3 monts of treatment with low dose formulation for ccHT containing 1 mg of estradiol and 0.5 mg of NETA, libido improves significantly.